2009
DOI: 10.3748/wjg.15.3687
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive ileus due to a giant fibroepithelial polyp of the anus

Abstract: Fibroepithelial polyps or hypertrophied anal papillae are essentially skin tags that project up from the dentate line and the junction between the skin and the epithelial lining of the anus. They are usually small in size, but sometimes they become enlarged, causing unexpected medical conditions. An extremely rare case of a giant hypertrophied anal papilla complicated by obstructive ileus is reported. Fibroepithelial anal polyp, despite its size, should be included in the differential diagnosis of a smooth mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 7 publications
(6 reference statements)
0
15
0
1
Order By: Relevance
“…There also has been a case of an anal fibroepithelial polyp treated with surgical resection because of associated obstructive ileus. 3 To our knowledge, this is the first case report of a giant fibroepithelial polyp presenting as a high-grade small bowel obstruction successfully managed with surgical resection.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…There also has been a case of an anal fibroepithelial polyp treated with surgical resection because of associated obstructive ileus. 3 To our knowledge, this is the first case report of a giant fibroepithelial polyp presenting as a high-grade small bowel obstruction successfully managed with surgical resection.…”
mentioning
confidence: 79%
“…2 Rarely, these polyps found in the anus have been associated with obstructive ileus of the gastrointestinal tract. 3 However, small bowel obstruction secondary to a fibroepithelial polyp of the small bowel has never been reported.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Küçük çaplı FAP'lerde belirgin bir semptom izlenmezken büyük olan FAP'lerde anüste kaşıntı, ağrı, kalıntı hissi, yabancı cisim hissi, kanama, ağrılı dışkılama gibi belirtiler görülebilmektedir [5,8,10]. Hatta obstrüktif ileusa bile neden olabilirler [11]. Bizim çalışmamızda en sık görülen belirtiler anüste ağrı ve kaşınma hissiydi.…”
Section: Discussionunclassified
“…2 A prospective cohort study suggested that fibroepithelial polyps of anus should be removed during anal fissure surgery, which would add to effectiveness and completeness of the procedure, and improve symptoms and patient's satisfaction. 3 In conclusion, fibroepithelial polyp of anus is a benign disease, and endoscopic polypectomy could be an alternative choice of treatment if it becomes enlarged and symptomatic.…”
Section: Answer To the Clinical Challenges And Images In Gi Question:mentioning
confidence: 99%